Prevalence of depression in patients with cancer in Iran: a systematic review and meta-analysis. Issue Volume 12:Issue e4(2022) (4th April 2019) - Aryankhesal, Aidin; Ghashghaee, Ahmad; Sardari, Elnaz; Mahmoudi, Sara; Alihosseini, Samira; Dehnad, Afsaneh; Roohravan Benis, Mahshid; Gharagozlou, Dorsa
Abstract : Introduction: It is generally accepted that depression, affecting the quality of life, is a serious and common complication in patients with cancer. Given that there is no integrated study on this topic in Iran, the present study sought to investigate the prevalence of depression in patients with cancer by a systematic review and meta-analysis. Methods: To meet the study objectives, all English and Persian papers published from 2000 to January 2018 were systematically collected and the data were extracted for analysis. Results: There were 14 studies which were selected on the basis of the inclusion and exclusion criteria. A total number of 2831 patients with cancer had participated in the studies. The prevalence of depression among Iranian patients with cancer was 35% (95% CI 16% to 70%) based on random effects model. Among various types of cancer, the highest prevalence of depression appeared to patients suffering from breast cancer. Conclusion: The prevalence of depression among patients with cancer in Iran was higher than the developed countries. As depression affects the quality of life of patients with cancer, the results can help policymakers and service providers in planning to reduce the prevalence of depression.